I love the mountains - Anderson, Steven; Wilkinson, Annie (North Mankato, MN Cantata Learning, 2016)
In this sing-along science song, a girl and her father go hiking and camping in the mountain. Walk along with them to hear why all the animals sing
English stories
1 2 13
NEW_ZTN_GN
Keywords: Children's songs -- Texts; Counting -- Songs and music -- Juvenile fictions; Mountains -- Songs and music -- Juvenile fiction; Nature -- Songs and music -- Juvenile fiction